Analisis Faktor-Faktor yang Mempengaruhi Permintaan Pasar terhadap UMKM Makanan Tradisional - Manalu, Erlin (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
The demand for traditional food SMEs (Small and Medium Enterprises) is influenced by various factors, including marketing strategies, business location, product innovation, and consumer preferences. This study aims to analyze the key determinants affecting market demand for traditional food SMEs by conducting a systematic literature review. Several studies indicate that digital marketing plays a crucial role in expanding the market reach and increasing competitiveness. Social media platforms such as Instagram, Facebook, and TikTok have proven effective in enhancing brand awareness and attracting new customers. Furthermore, geographical location significantly influences consumer interest, as strategic business placement can increase sales volume. Product innovation, including variations in taste and packaging design, also contributes to consumer purchasing decisions. However, challenges such as technological adaptation, regulatory constraints, and access to capital remain obstacles for traditional food SMEs. The findings highlight the importance of integrating digital and conventional marketing strategies, optimizing business locations, and maintaining product authenticity while innovating. Future research should focus on developing sustainable marketing strategies and addressing regulatory challenges to support the growth of traditional food SMEs in Indonesia.